ANALISIS PEMILIHAN METODE RESERVASI DI HOTEL MERCURE BATAM - Teja Kumaro Prajnagaja; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to discover determining factors for reservation methods amongst customers in Mercure Hotel, Batam, Indonesia.In order to inspect the core issue of the chosen topic, writer has applied quantitative descriptive method to build this paper. The research’s sample is constructed through 150 people in a dedicated focus group, while the collection technique is assembled through observations, interviews and documentations. Based on Likert’s scale theory, writer will demonstrate four indicators as the main influencers for Mercure Hotel; Ease, Rates, Trustworthiness and Awareness.Based on aforementioned examinations, conclusively the main deciding factors for customer direct reservation is ease and trustworthiness. On the other hand, customer through company/event/travel agent reservations will most likely make hotel reservation based on rates and trustworthiness; Customers with Affiliate Reservation Network will prioritize trustworthiness while those with Non-Affliliate Reservation Networks will opt for most value rates.Keywords: Room Reservation, Reservation Method, Reservation